Expression of Connexins 43, 26 and 32 in normal, hyperplastic and neoplastic perianal dog glands - Martins, Ana Maria C. R. P. F.; Guerra, José L.; Oloris, Silvia C. S.; Avanzo, José L.; Lima, Cyntia E. de; Dagli, Maria L. Z. (Brazilian Journal of Veterinary Pathology, 2010)
Connexin (Cx) expression is reportedly altered in neoplasms. This study aimed to investigate the expression of Cx43, 26 and 32 in normal and pathological canine perianal glands. Thirty perianal glands bearing pathological processes and ten normal canine perianal glands were submitted to immunohistochemistry to search for presence of Cx43, Cx26 and Cx32. Both Cx43 and Cx26 expressions were observed in normal, hyperplastic glands, and in well and moderately differentiated adenomas. However, in poorly differentiated adenomas, expressions were reduced, and they were absent in carcinomas. Cx26 was located in the cytoplasm of normal, hyperplastic perianal gland cells, and in well and moderately differentiated adenomas. Cx32 was not observed in any neoplasm neither in normal or hyperplastic glands. Our results show that Cx43 and Cx26 expressions are altered in more aggressive canine perianal gland neoplasms, and we conclude that they may be related to the perianal gland carcinogenesis process.